86 The Effect of Blood Pressure in Arterial Stiffness in Diabetes Mellitus: Preliminary Study. (November 2017) - Darnindro, Nikko
Abstract : Background: Micro and macro-vascular complications in diabetic patients were caused by atherosclerosis. Hypertension is one of the comorbidities often found in patients with diabetes. The combination of diabetes and hypertension increase the risk of atherosclerosis. The cardio-ankle vascular index (CAVI) has been widely accepted as a good indicator of atherosclerosis but limited data exist to determine the value of CAVI. Objective: To determine the value of CAVI in hypertensive diabetic patients Methods: Cross sectional study was conducted in Cilincing General Hospital in adults with diabetes and normal Ankle-Brachial Index. CAVI was measured at rest with VASERA 1500N FUKUDA-DENSHIand considered normal (CAVI < 8), borderline (8 ⩽ CAVI < 9), or abnormal with subclinical atherosclerosis (CAVI ≥ 9). Result: We studied 37 patients (23.7% men and 76.3% women; mean age 57.9 +/- 9.7 years; Mean CAVI was 8.6 +/- 2.3. Abnormal and borderline CAVI were detected in 45.9% and 27% patients. Mean CAVI increased inhypertension patients, More patients with hypertension have abnormal CAVI value (53.3% vs 40.9%). Proportion of abnormal CAVI was higher as sistolic, diastolic and mean arterial pressure increased. Conclussion: Prevalence of abnormal CAVI was high in diabetic patients. Proportion of abnormal CAVI was higher as blood pressure increased. Early screening of atherosclerosis in hypertensive diabetic patients are urgently needed.